Immunotherapy in Non–Small Cell Lung Cancer Treatment: Current Status and the Role of Imaging. Issue 5 (September 2017) - Carter, Brett W.; Halpenny, Darragh F.; Ginsberg, Michelle S.; Papadimitrakopoulou, Vassiliki A.; de Groot, Patricia M.
Abstract : Lung cancer remains the leading cause of cancer-related mortality and is responsible for more deaths than breast, prostate, and colon cancer combined. Most patients are diagnosed with advanced disease at the time of presentation, and treatment options have traditionally included surgery, chemotherapy, and/or radiation. However, significant advances in the molecular characterization of lung cancer have led to the creation of effective immunotherapies that assist in the recognition of cancer as foreign by the host immune system, stimulate the immune system, and relieve the inhibition that allows tumor growth and spread. Extensive experience with the immunomodulatory monoclonal antibody ipilimumab has demonstrated that unique responses may be seen with immunotherapies that are not adequately captured by traditional response criteria such as the World Health Organization criteria and Response Evaluation Criteria in Solid Tumors (RECIST). Consequently, several modified criteria have been developed to evaluate patients treated with immunotherapy, including immune-related response criteria, immune-related RECIST, and immune RECIST. Finally, patients undergoing immunotherapy may develop a wide variety of immune-related adverse events with which the radiologist must be familiar. In this article, we present the fundamental concepts behind immunotherapy, specific agents currently approved for the treatment of lung cancer, and immune-related adverse events. The role of imaging in the evaluation of these patients will also be discussed, including the general principles of treatment response evaluation, specific response criteria adopted with these agents, including immune-related response criteria, immune-related RECIST, and immune RECIST, and the imaging of immune-related adverse events.